Pengaruh Resource-Based View terhadap Innovation Performance pada UMKM Ekspor: Peran Moderasi Government Information Access: Studi Kasus pada CV. Delta Raya - Rina Maretasari; Sudarmiatin Sudarmiatin; Puji Handayati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Resource-Based View (RBV) on innovation performance in Micro, Small, and Medium Enterprises (MSMEs) that have expanded internationally, with government information access as a moderation variable. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The object of the research is CV. Delta Raya, an MSME in the furniture sector from Batu City that has successfully penetrated the export market to Japan, South Korea, and Mexico. The results of the study show that human capital investment and political connections have a significant positive effect on innovation performance. Although international experience does not have a direct effect, the effect becomes significant when moderated by government information access. Access to government information also strengthens the influence of political connections on innovation. The implications of this study underscore the importance of collaboration between MSME actors and government institutions in encouraging internal resource-based innovation.